SEARCH ENGINE OPTIMIZATION IN INTERNET MARKETING UNDER THE TRANSFORMATION OF GENERATIVE ARTIFICIAL INTELLIGENCE: FROM GOOGLE TO CHATGPT - RODIONOV, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the transformation of approaches to search engine optimization (SEO) in the context of the rapid integration of generative artificial intelligence (AI) into the digital information space. Traditional SEO, which focuses mainly on improving website visibility in search engines like Google, is gradually losing its dominant role. This shift is driven by changes in user behavior and the growing influence of AI-based assistants such as ChatGPT, xAI, Gemini, and similar tools.The research highlights how generative AI models are becoming primary sources of information for users, replacing standard search engines in many situations. As a result, businesses, content creators, and digital marketers must adapt their optimization strategies to ensure their content is accessible, relevant, and useful for AI-driven systems. Unlike traditional SEO, which relies heavily on keywords, backlinks, and search engine algorithms, the new approach must consider how AI models process, rank, and generate responses based on existing digital content.The paper argues for the need to develop a new set of optimization practices — referred to as AIO (Artificial Intelligence Optimization) — which would complement traditional SEO techniques. AIO focuses on structuring content in a way that improves its visibility and usability for generative AI tools. This includes writing clear and informative text, using structured data, and ensuring factual accuracy, as AI models prioritize well-organized and reliable sources.Furthermore, the study outlines key differences between SEO and AIO and proposes recommendations for integrating AIO strategies into existing content workflows. By combining SEO with AIO, organizations can increase their chances of being featured not only in search engine results but also in AI-generated responses.
Keywords: search engine optimization; generative artificial intelligence; marketing; AIO; ChatGPT; xAI; Gemini; digital strategy